2018
DOI: 10.1186/s13640-018-0266-x
|View full text |Cite
|
Sign up to set email alerts
|

A head-mounted goggle-type video-oculography system for vestibular function testing

Abstract: Disorders of the vestibular system possibly decrease vision, causing abnormal nystagmus and dizziness. To diagnose abnormal nystagmus, various studies have been reported including the use of rotating chair tests and videonystagmography. However, these tests are unsuitable for home use due to their high costs. Thus, a low-cost video-oculography system is necessary to obtain clinical features at home. In this paper, we present a goggle-type low-cost video-oculography system using an infrared camera and Raspberry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Furthermore, Lee and Kim [8] reported that sports VR training significantly influenced coordination related to balance and postural stability. In addition to this, various studies have found that VR simulation-based exercise increases body stability [27][28][29]. In other words, we can predict the mechanism by which VR increases action duration, as seen in this study: a sense of balance can enhance the stable continuation of a certain posture.…”
Section: Comparison To Prior Workmentioning
confidence: 64%
“…Furthermore, Lee and Kim [8] reported that sports VR training significantly influenced coordination related to balance and postural stability. In addition to this, various studies have found that VR simulation-based exercise increases body stability [27][28][29]. In other words, we can predict the mechanism by which VR increases action duration, as seen in this study: a sense of balance can enhance the stable continuation of a certain posture.…”
Section: Comparison To Prior Workmentioning
confidence: 64%
“…Therefore, appropriate sports VR training (game-based) is seen as an important factor in the trunk alignment, and it also affects the strength, balance, and quality of life of the lower extremities. Recently, studies with various age groups and materials included VR gears [14,[16][17][18] have been continuing and have been taking place as an effective training method. In this study, sports VR training which may be helpful for aerobic exercise and may strengthen cardiopulmonary showed better effect on coordination (body composition).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most popular SBC devices is the Raspberry Pi [25]. Indeed, it is used in many research works, as in a distributed system for pollution monitoring on a smart city [24], in image processing [26,27] and educational [28] fields.…”
Section: Instrument Specificationmentioning
confidence: 99%